Menopause and development of Alzheimer’s disease: Roles of neural glucose metabolism and Wnt signaling - Villaseca, Paulina; Cisternas, Pedro; Inestrosa, Nibaldo C. (Frontiers in Endocrinology, 2022)
Late onset Alzheimer´s disease (AD) is a neurodegenerative disease with gender differences in its onset and progression, being the prevalence predominant in women and at an earlier age than in men. The pathophysiology of the menopausal condition has been associated to this dementia, playing major roles regarding both endocrine and glucose metabolism changes, amongst other mechanisms. In the current review we address the role of estrogen deficiency in the processes involved in the development of AD, including amyloid precursor protein (APP) processing to form senile plaques, Tau phosphorylation forming neurofibrillary tangles, Wnt signaling and AD neuropathology, the role of glucose brain metabolism, Wnt signaling and glucose transport in the brain, and our research contribution to these topics.